2014
DOI: 10.1371/journal.pone.0088841
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Three Serum Phospholipid Panel Differentiates Normal Individuals from Those with Prostate Cancer

Abstract: BackgroundThe results of prostate specific antigen (PSA) and digital rectal examination (DRE) screenings lead to both under and over treatment of prostate cancer (PCa). As such, there is an urgent need for the identification and evaluation of new markers for early diagnosis and disease prognosis. Studies have shown a link between PCa, lipids and lipid metabolism. Therefore, the aim of this study was to examine the concentrations and distribution of serum lipids in patients with PCa as compared with serum from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…The potential repercussion of these data is the use of PLs' FAs as biomarkers of breast cancer and as potential targets for treatment, pending appropriate investigations. This is in accordance with Patel et al [71], who reported three types of PC in prostate cancer cells as biomarkers of progression. Liver cancer is also interesting in terms of PL and health.…”
Section: Effects Of Pls On Cancersupporting
confidence: 93%
“…The potential repercussion of these data is the use of PLs' FAs as biomarkers of breast cancer and as potential targets for treatment, pending appropriate investigations. This is in accordance with Patel et al [71], who reported three types of PC in prostate cancer cells as biomarkers of progression. Liver cancer is also interesting in terms of PL and health.…”
Section: Effects Of Pls On Cancersupporting
confidence: 93%
“…The cut-off values derived in the tested serum (ePC 38:5 > 0.015 nmoles, PC 40:3 < 0.001 nmoles and PC 42:4 < 0.0001 nmoles) were associated with a predictability of 94% for the absence of prostate cancer; whereas for the cut-off value of ePC 38:5 < 0.015 nmoles, PC 40:3 > 0.001 nmoles, and PC 42:4 > 0.0001 nmoles, the predictability of prostate cancer disease was high. The authors concluded that a combination of serum ePC 38:5, PC 40:3 and PC 42:4 could be predictive for detecting prostate cancer, if confirmed in a larger dataset [70]. Duscharla and co-workers recently employed ESI-MS/MS and GC-MS in an effort to identify significantly altered lipids in serum of prostate cancer patients.…”
Section: Lipidomics In Cancer Researchmentioning
confidence: 99%
“…Among these different ionization techniques, ESI has gained significant importance in lipidomic analysis. Several investigators have used ESI tandem MS experiments (ESI‐MS/MS and MS n ) in combination with separation methods (TLC and HPLC) to profile and structurally characterize PLs in various cancer cells, tissues, and biofluids like plasma, serum, and urine (Xiao et al, ; Kim et al, ; Min, Kong, & Moon, , ; Jeong et al, ; Patterson et al, ; Doria et al, ; Liu et al, ; Tan et al, ; Patel et al, ). The product‐ions from positive‐ and negative‐ion ESI tandem MS experiments usually provide specific information about the polar head group (Ekroos et al, ; Thomas et al, ), composition of PLs and FAs, clear‐cut structural characterization and identification of PL class (Table ).…”
Section: Electrospray Ionization and Matrix‐assisted Laser Desorptionmentioning
confidence: 99%
“…They observed the increased concentrations of some high‐abundant PL species PE(14:0/14:0), PG(16:2/16:0) and PA (20:6/18:1) from the normal prostate epithelial cell line (PrEC), whereas it had a negligible effect on the same PL species from the prostate cancer cell lines (DU145 and LNCaP). Patel et al () analyzed the distribution and concentrations of serum lipids in patients and healthy subjects with ESI‐MS/MS analysis. The results showed that lipid species, PC, egg PC (ePC), egg PE (ePE), and dihydro SM (dSM) are varied in the serum between normal and cancer patients.…”
Section: Ms‐based Analysis Of Pls In Various Cancers and Biomarker DImentioning
confidence: 99%